2005
DOI: 10.1038/sj.ijir.3901369
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hypogonadism in men based upon age, presence of erectile dysfunction, and depression

Abstract: Hypogonadism, a disorder associated with aging, can cause significant morbidity. As clinical manifestations of hypogonadism can be subtle, the challenge and the burden of diagnosis remain the responsibility of the clinician. Four different analytic methods were used to predict hypogonadism in men based upon age, the presence of erectile dysfunction (ED) and depression. 218 men were classified by age, serum testosterone level, the presence of ED and depression. Depression was determined by the Center for Epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…In fact, we have previously shown that depression scores can be used as a clinical aid to predict hypogonadism using an artificial neural network model. 24 The present study lends further support to this concept.…”
Section: Discussionsupporting
confidence: 73%
“…In fact, we have previously shown that depression scores can be used as a clinical aid to predict hypogonadism using an artificial neural network model. 24 The present study lends further support to this concept.…”
Section: Discussionsupporting
confidence: 73%
“…Sexual symptoms are therefore of diagnostic importance in elderly men but should suggest androgen deficiency only when testosterone levels are clearly sub-normal 325. The presence of multiple symptom-specific testosterone thresholds indicates that different functional thresholds exist for different androgen-dependent targets 326293031. Our study suggests that some symptoms of LOH may manifest at higher concentrations of androgens than other symptoms ( Table 2 ), which suggest that testosterone thresholds may be symptom-specific26 or that the phenotype upon which the symptoms of androgen deficiency are based does not apply in all respects to aging men 32.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the above observations it is clear that the symptoms of testosterone deficiency are not uniformly and predictably related to values of blood testosterone, which may lead to different diagnostic criteria for testosterone deficiency. So, the conclusion seems inevitable that the clinical manifestations of hypogonadism are multifactorially determined and that the diagnosis should not only depend on the measurement of testosterone but proper assessment should comprise somatic and psychological npg aspects in addition to measurement of testosterone [29].…”
Section: Thresholds and Dose-response Relationships Of Androgen Effectsmentioning
confidence: 99%